Intrauterine exposure to diesel exhaust diminishes adult ovarian reserve - Ogliari, Karolyn Sassi; Lichtenfels, Ana Julia De Faria Coimbra; Marchi, Mary Rosa Rodrigues de [UNESP]; Ferreira, Alice Teixeira; Dolhnikoff, Marisa; Saldiva, Paulo Hilario Nascimento (Elsevier, 2013)
Objective To analyze ovarian and uterine morphologic changes resulting from intrauterine and postnatal exposure to diesel exhaust. Design Crossover study. Experimental groups: intrauterine and postnatal clean air exposure; intrauterine exposure to diesel only; postnatal exposure to diesel only; and intrauterine and postnatal exposure to diesel. Setting Laboratory of Experimental Air Pollution. Animal(s) Swiss mice. Intervention(s) Mice exposed to diesel exhaust with doses that correspond to the daily average PM2.5 levels (fine particles in the ambient air 2.5 μm or less in size) reported by the World Health Organization. Main Outcome Measure(s) Morphometric analyses of the ovaries and uterus were performed to define the relative area occupied by follicles, corpus luteum, and stroma and the proportionate area of glands, epithelial layer, and stroma within the uterine endometrium. Result(s) A significant reduction in the proportion of primordial follicles was observed in intrauterine-exposed animals, those exposed during the postnatal period, and in animals exposed during both phases. Primary follicle proportion was reduced in animals exposed during pregnancy. No significant changes were detected in uterine morphology. Conclusion(s) Intrauterine exposure to acceptable levels of diesel exhaust compromises the reproductive potential of female mice, diminishing ovarian reserve when sexual maturity is achieved. This effect could increase the risk of premature menopause. The findings raise concern about current environmental guidelines for diesel exposure, warranting more careful examination of this issue in humans by regulatory authorities.
Keywords: Ovarian follicle; Menopause; Vehicle emissions; Mice